A Geometric Modelling in the CAD System from the Medical Images to Support Prosthesis Design - Canciglieri Junior, Osiris; Rudek, Marcelo; Francesconi, Tiago; Souza, Teofilo Miguel de [UNESP]; Pokojski, J.; Fukuda, S.; Salwinski, J. (Springer, 2010)
This paper discusses the feasibility of individually designing human prosthesis for surgical use and proposes a methodology for such design through mathematical extrapolation of data from digital images obtained via tomography of individual patient's bones. Individually tailored prosthesis designed to fit particular patient requirements as accurately as possible should result in more successful reconstruction, enable better planning before surgery and consequently fewer complications during surgery. Fast and accurate design and manufacture of personalized prosthesis for surgical use in bone replacement or reconstruction is potentially feasible through the application and integration of several different existing technologies, which are each at different stages of maturity. Initial case study experiments have been undertaken to validate the research concepts by making dimensional comparisons between a bone and a virtual model produced using the proposed methodology. Future research directions are discussed in the final section of this paper.
Keywords: Geometric modeling; CAD; human prosthesis; image processing; medical information; tomography examination